Religion and immigration : migrant faiths in North America and Western Europe. - Kivisto, Peter (Immigration & society., 2014)
This concise book provides readers with a comprehensive overview and critical assessment of the key issues and varied strands of research relating to immigration and religion that have been produced during the past two decades.